2019
DOI: 10.1021/acs.chemrev.8b00539
|View full text |Cite
|
Sign up to set email alerts
|

Halide Perovskite Photovoltaics: Background, Status, and Future Prospects

Abstract: The photovoltaics of organic−inorganic lead halide perovskite materials have shown rapid improvements in solar cell performance, surpassing the top efficiency of semiconductor compounds such as CdTe and CIGS (copper indium gallium selenide) used in solar cells in just about a decade. Perovskite preparation via simple and inexpensive solution processes demonstrates the immense potential of this thin-film solar cell technology to become a low-cost alternative to the presently commercially available photovoltaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
1,938
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,377 publications
(1,963 citation statements)
references
References 461 publications
17
1,938
0
8
Order By: Relevance
“…While R S is only affecting the FF, the lower J SC and V OC observed for the 4 mol% device could be caused by the lower R rec obtained for this sample (see Figure S8b in the Supporting Information). 2019, 9,1901519 Figure 1. a) UV-vis absorption spectra of HTM films doped with spiro-OMeTAD(TFSI) 2 (inset: absorption coefficient (α) of the spiro-OMeTAD(TFSI) 2 -doped spiro-OMeTAD films). It is worth noting that the large R HTM of the pristine spiro-OMeTAD is not enough to explain the low PCE of the sample (see Figure S9d in the supporting information) for extended analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While R S is only affecting the FF, the lower J SC and V OC observed for the 4 mol% device could be caused by the lower R rec obtained for this sample (see Figure S8b in the Supporting Information). 2019, 9,1901519 Figure 1. a) UV-vis absorption spectra of HTM films doped with spiro-OMeTAD(TFSI) 2 (inset: absorption coefficient (α) of the spiro-OMeTAD(TFSI) 2 -doped spiro-OMeTAD films). It is worth noting that the large R HTM of the pristine spiro-OMeTAD is not enough to explain the low PCE of the sample (see Figure S9d in the supporting information) for extended analysis.…”
Section: Resultsmentioning
confidence: 99%
“…An intense emission was observed at 765 nm for the neat perovskite. 2019, 9,1901519 more efficient charge transfer in the former. Energy Mater.…”
Section: Resultsmentioning
confidence: 99%
“…[5] However, it also limits their stability against moisture and polar solvents. [5] However, it also limits their stability against moisture and polar solvents.…”
Section: The Challengesmentioning
confidence: 99%
“…Interestingly, it has been reported that the addition of Br − into MAPbI 3−x Br x increased the PCE and the resistance to humidity. [5] www.advsustainsys.com [29] Besides resistance to humidity, photostability is of particular interest.…”
Section: The Challengesmentioning
confidence: 99%
See 1 more Smart Citation